2000
DOI: 10.1111/j.1741-3729.2000.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

The Care Continues: Responsibility for Elderly Relatives Before and After Admission to a Long Term Care Facility*

Abstract: Interviews with 214 family members are analyzed to investigate how caregiving changes from the community to the long term care (ltc) facility and to understand family member's responsibility toward elderly relatives in ltc facilities. Family responsibilities can be categorized as 'indirect' including an overseer of care or 'direct' including performing specific tasks. Findings suggest that emotional support needs to be incorporated into measures of caregiving. Research implications include the need for increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 30 publications
6
47
1
8
Order By: Relevance
“…There is a considerable body of literature on the guilt experienced by carers as they place their care receiver in a nursing home (Keefe & Fancey, 2000;Kellett, 1999). However, there is less literature examining experiences of guilt during the post-death transition.…”
Section: The Thrush Was That Bad It Was Coming Out His Lip I Supposementioning
confidence: 99%
See 4 more Smart Citations
“…There is a considerable body of literature on the guilt experienced by carers as they place their care receiver in a nursing home (Keefe & Fancey, 2000;Kellett, 1999). However, there is less literature examining experiences of guilt during the post-death transition.…”
Section: The Thrush Was That Bad It Was Coming Out His Lip I Supposementioning
confidence: 99%
“…The transition and post-placement period were viewed as an extremely stressful time due to the complex feelings associated with placement as well as the strain of negotiating new relationships with the staff and the relative (Noonan et al, 1999;Pearson et al, 2003;Wackerbarth, 1999). Research studies have also identified a wide array of complex emotions for the carer including guilt, anxiety, sadness, relief, a sense of failure, disempowerment and a loss of control (Argyle et al, 2010;Keefe & Fancey, 2000;Kellett, 1999).…”
Section: 3a Research Findings On the Post-caring/ Care Transitions mentioning
confidence: 99%
See 3 more Smart Citations